2009
DOI: 10.1051/dst/2009010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of trace elements and calcium on diabetes and obesity, and their complications: Protective effect of dairy products – A mini-review

Abstract: -Trace elements and minerals influence the pathogenesis of obesity and diabetes and their complications, mainly through their involvement in peroxidation and inflammation. On the other hand, peroxidation and inflammation are liable to alter the metabolism of these nutrients, which should be taken into account when assessing their status. Milk products are capable of preventing iron-induced peroxidation and the metabolic complications of the diseases. Calcium, especially cow milk calcium, seems to be capable of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
(33 reference statements)
1
0
0
Order By: Relevance
“…The results of logistic regression, shown in Table 4, revealed that milk (either fresh milk with sugar or condensed milk) reversed the relationship with overweight status. This result agreed with other studies suggesting that there was a protective effect of milk against obesity, 30,31 probably due to calcium and other factors in the milk, 32 which potentially have a major influence over the children's physical development too. 33,34 Unfortunately, the price of milk and milk products are relatively high in Vietnam and impede the benefits that these products could bring to most of the population, especially children and adolescents.…”
Section: Discussionsupporting
confidence: 92%
“…The results of logistic regression, shown in Table 4, revealed that milk (either fresh milk with sugar or condensed milk) reversed the relationship with overweight status. This result agreed with other studies suggesting that there was a protective effect of milk against obesity, 30,31 probably due to calcium and other factors in the milk, 32 which potentially have a major influence over the children's physical development too. 33,34 Unfortunately, the price of milk and milk products are relatively high in Vietnam and impede the benefits that these products could bring to most of the population, especially children and adolescents.…”
Section: Discussionsupporting
confidence: 92%